A revision of Leopoldinia (Arecaceae) - Henderson, Andrew (Phytotaxa, 2011)
A taxonomic revision of the Neotropical palm genus Leopoldinia based on morphological data and morphometric methods was carried out. One hundred and sixteen herbarium specimens were scored for seven qualitative and 24 quantitative variables. Qualitative variables were divided into six characters and one trait. Using the Phylogenetic Species Concept, the six characters were used to recognize three species. These are widely distributed in the central Amazon region of Brazil and adjacent Venezuela and Colombia. Nomenclature, descriptions, illustrations, and distribution maps are provided for each taxon.